A retrospective study of posterior canal benign paroxysmal positional vertigo cases in a tertiary care industrial hospital - Sahoo, Soumick Ranjan; Nayak, Pallavi; Datta, Nilanjan (International Journal of Otorhinolaryngology and Head and Neck Surgery, 2024)
Background: Balance disorders form a significant proportion of the patients attending ENT OPD. Among the various otologic causes responsible for balance disturbances, BPPV is one of the important causes. The etiological mechanism responsible for BPPV are canalithiasis and cupulolithiasis. Positional maneuver such as Epleys maneuver are used for treating posterior canal BPPV along with medications. Methods: We are retrospectively studying the posterior canal BPPV cases seen in our hospital from January 2022 to January 2024. There were total 192 vertigo cases seen in the vertigo clinic of ENT Department after taking into account inclusion and exclusion criteria. Diagnosed cases of posterior canal BPPV were treated by Epleys maneuver along with pharmacological treatment. Results: Total 50 cases of posterior canal BPPV were diagnosed which constituted 26.04% of the total no of vertigo cases. Regarding the etiology of posterior canal BPPV, 2 cases were posttraumatic while 48 cases were idiopathic. The success rate of Epleys maneuver along with Betahistine was 78% in treating such cases. Conclusions: This retrospective study shows that most of the posterior canal BPPV cases were idiopathic. Epleys maneuver along with Betahistine was effective in the management of BPPV patients in our setup.